Chronic inhibition of lipoprotein-associated phospholipase A2 does not improve coronary endothelial function: A prospective, randomized-controlled trial. (15th February 2018) - Prasad, Megha; Lennon, Ryan; Barsness, Gregory W.; Prasad, Abhiram; Gulati, Rajiv; Lerman, Lilach O.; Lerman, Amir
Abstract: Aims: Lipoprotein-associated phospholipase A2 (Lp-PLA2 ), a novel biomarker for vascular inflammation, is associated with coronary endothelial dysfunction (CED) and independently predicts cardiovascular events. The current study aimed to determine whether darapladib, an orally administered Lp-PLA2 inhibitor, improved CED. Methods and results: Fifty-four patients with CED were enrolled in a double-blinded randomized placebo-controlled trial, and were randomized to receive oral darapladib, 160 mg daily, or placebo. Coronary angiography and invasive coronary endothelial function assessment were performed at baseline and post-6 months of treatment. Primary endpoints were change in coronary artery diameter and coronary blood flow in response to acetylcholine. Additionally, Lp-PLA2 activity was measured at baseline and on follow-up to evaluate for adherence and drug effect. Fifty-four patients were randomized to placebo ( n  = 29) and darapladib ( n  = 25). Mean age in darapladib group was 55.2. ± 11.7 years vs. 54.0 ± 10.5 years ( p  = 0.11). On follow-up, there was no significant difference in the percent response to acetylcholine of coronary artery diameter in treatment vs. placebo group (+ 3 (IQR − 9, 15) vs. + 3 (− 12, 19); p  = 0.87) or coronary blood flow (− 5 (IQR − 24, 54) vs. 39 (IQR − 26, 67); p  = 0.41). There was significant reduction in Lp-PLA2 activity in the treatment arm vs. placebo (− 76 (IQR − 113, − 52) vs. − 7(− 21, − 7); p  < 0.001). Discussion: Lp-PLA2 inhibition with darapladib did not improve coronary endothelial function, despite significantly reduced Lp-PLA2 activity with darapladib. This study suggests endogenous Lp-PLA2 may not play a primary role in coronary endothelial function in humans. Clinicaltrials.gov Identifier: NCT01067339